Industrial Use of Cell Wall Degrading Enzymes: The Fine Line Between Production Strategy and Economic Feasibility - Giovannoni, Moira; Gramegna, Giovanna; Benedetti, Manuel; Mattei, Benedetta (Frontiers in Bioengineering and Biotechnology, 2020)
Cell wall degrading enzymes (CWDEs) are a heterogeneous group of enzymes including glycosyl-hydrolases, oxidoreductases, lyases and esterases. Microbes with degrading activities towards plant cell wall polysaccharides are the most relevant source of CWDEs for industrial applications. These organisms secrete a wide array of CWDEs in amounts strictly necessary for their own sustenance, nonetheless the production of CWDEs from wild type microbes can be increased at large-scale by using optimized fermentation strategies. In the last decades, advances in genetic engineering allowed the expression of recombinant CWDEs also in lab-domesticated organisms such as E. coli, yeasts and plants, dramatically increasing the available options for the large-scale production of CWDEs. The optimization of a CWDE-producing biofactory is a hard challenge that biotechnologists tackle by testing different expression strategies and expression-hosts. Although both the yield and production costs are critical factors to produce biomolecules at industrial scale, these parameters are often disregarded in basic research. This review presents the main characteristics and industrial applications of CWDEs directed towards the cell wall of plants, bacteria, fungi and microalgae. Different biofactories for CWDE expression are compared in order to highlight strengths and weaknesses of each production system and how these aspects impact the final enzyme cost and, consequently, the economic feasibility of using CWDEs for industrial applications.